Pembebanan Hak Tanggungan pada Hak Guna Bangunan diatas Hak Milik - Nastiti, Althea salza; Darmawan, Madeleine Evania; Irawan, Deny; Arifah, Nurmalita Fajar (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Debt guarantees attached to building use rights above property rights are prone to problems, especially if there is default or there has been no repayment but the building use rights have expired. Based on that, this study aims to analyze the imposition of Mortgage Rights on land with building use rights on property rights and explain the legal protection for creditors as the holder of Mortgage Rights. The type of research that will be used is normative research. In this study will use a statutory approach or statute approach. The data collection technique used was literature study with prescriptive analysis techniques. The results of this study indicate that building use rights over property rights can be charged with mortgage rights. The creditor as the party holding the Mortgage must apply the precautionary principle in the event of default by the debtor. As for the legal protection that can be applied to the imposition of Mortgage Rights on building use rights over property rights through the Deed of Granting Mortgage Rights. This is to accommodate if the process of carrying out the Mortgage auction takes a long time, so that it will affect the term of the right to use the building over the right of ownership. Creditors are also given the authority to renew building use rights over property rights as one of the efforts to prevent the erasure of building use rights over said property rights.